High-strength modified plastic product and preparation process thereof

By blending modified carbon fiber with flame retardant and other materials with PPA and molding with twin screw extruders, the combustion and thermal degradation problems of PPA materials in high temperature environments are solved, the mechanical properties and flame retardant properties of the materials are significantly improved, and high-strength and high-performance modified plastic products are achieved.

CN119570247AActive Publication Date: 2025-03-07广东精宏健智控科技有限公司

Patent Information

Application Number
CN202411787486.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

In some applications, existing PPA materials have problems such as insufficient toughness, poor processing performance and limited flame retardant properties, especially in high temperature environments, which are prone to combustion and thermal degradation.

Method used

By mixing modified carbon fibers, flame retardants, photoinitiators and N,N-dimethylformamide evenly, irradiated, washed and dried by ultraviolet light, blending with polyphthalamide (PPA), melt extrusion, granulation and injection molding using a twin-screw extruder, high-strength modified plastic products were prepared.

Benefits of technology

It significantly improves the dispersion of carbon fiber in the PPA matrix, enhances the mechanical properties and flame retardant properties of the material, and thus achieves high-strength and high-performance modified plastic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of plastic materials, in particular to a high-strength modified plastic product and a preparation process thereof. The preparation method comprises the following steps: uniformly mixing modified carbon fibers, a flame retardant, a photoinitiator and N, N-dimethylformamide, and performing ultraviolet irradiation, washing and drying to obtain a compound; uniformly mixing polyphthalamide, the compound, polyethylene wax, an antioxidant and a nucleating agent to obtain a blend; and carrying out melt extrusion, granulation and injection molding on the blend in a twin-screw extruder to obtain the modified plastic product. The modified plastic product prepared by the invention not only has excellent mechanical properties, but also has excellent flame retardance, and the use safety and durability of the modified plastic product are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic materials, in particular to a high-strength modified plastic product and a preparation process thereof. Background Art

[0002] Polyphthalamide (PPA) is a semi-aromatic polyamide, commonly known as high-temperature resistant nylon. Due to its excellent heat resistance, chemical resistance, mechanical strength and dimensional stability, it has broad application prospects in the fields of electronics, automobiles, aerospace, etc. However, pure PPA materials still have some limitations in certain applications, such as insufficient toughness, processing performance and flame retardancy need to be improved.

[0003] The enhancement and flame retardant properties of PPA are mainly improved by filling flame retardants and carbon fibers. However, due to the lack of chemically active functional groups on the surface of carbon fibers, they are usually chemically inert, resulting in weak interfacial bonding between them and the PPA matrix, making it difficult to effectively exert the reinforcing effect of carbon fibers; in terms of flame retardant properties, the flame retardant properties of PPA itself are relatively limited, and it is easy to cause combustion and thermal degradation in high temperature environments.

[0004] Therefore, we propose a high-strength modified plastic product and a preparation process thereof. Summary of the invention

[0005] The purpose of the present invention is to provide a high-strength modified plastic product and a preparation process thereof to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A preparation process of a high-strength modified plastic product comprises the following steps: Step S1: uniformly mixing the modified carbon fiber, the flame retardant, the photoinitiator and N,N-dimethylformamide, irradiating with ultraviolet light, washing and drying to obtain a composite; Step S2: uniformly mixing polyphthalamide, the composite, polyethylene wax, an antioxidant and a nucleating agent to obtain a blend; melt-extruding, granulating and injection-molding the blend in a twin-screw extruder to obtain a modified plastic product.

[0007] Furthermore, the modified plastic product comprises the following components by weight: 35-65 parts of polyphthalamide, 30-60 parts of the composite, 0.2-0.4 parts of polyethylene wax, 0.2-0.6 parts of antioxidant, and 0.3-0.5 parts of nucleating agent.

[0008] Furthermore, the composite comprises the following components by weight: 20-45 parts of modified carbon fiber, 10-15 parts of flame retardant, 2-4 parts of photoinitiator, and 50-100 parts of N,N-dimethylformamide.

[0009] Furthermore, the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.

[0010] Furthermore, the preparation method of the modified carbon fiber is as follows: Step (1): adjusting the pH of Tris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a dopamine hydrochloride solution; immersing the pretreated carbon fiber in the dopamine hydrochloride solution for 20-24 hours, taking it out, and drying it to obtain a polydopamine-coated carbon fiber; Step (2): uniformly mix maleic anhydride and 1,4-dioxane, dropwise add a mixed solution of diethylenetriamine and 1,4-dioxane, and complete the dropwise addition for 1-2 hours, react at room temperature for 2-3 hours, and obtain a prepolymer monomer after vacuum distillation and drying; uniformly mix the prepolymer monomer and deionized water, add ethylenediamine, react at 85-95° C. for 4-5 hours, cool to room temperature, and obtain an amino-terminated hyperbranched polyamide after vacuum distillation and drying; Step (3): placing the polydopamine-coated carbon fiber in an aqueous solution of amino-terminated hyperbranched polyamide, ultrasonically treating for 1-2 hours, reacting for 3-5 hours, filtering and drying to obtain modified carbon fiber.

[0011] Furthermore, in step (1), the concentration of the Tris-HCl buffer is 0.01 mol / L, the concentration of the dopamine hydrochloride solution is 2-4 mg / mL, and the mass of the pretreated carbon fiber is 2-5% of the mass of the dopamine hydrochloride solution.

[0012] Furthermore, the preparation method of the pretreated carbon fiber is as follows: The carbon fiber is soaked in acetone for 22-24 hours to remove the sizing agent on the surface, and then cleaned with deionized water and dried to obtain the pretreated carbon fiber.

[0013] Furthermore, in the step (2), the mass ratio of maleic anhydride to 1,4-dioxane is 1:(4-5).

[0014] Furthermore, in step (2), the mass of diethylenetriamine is 1.1-1.3 times the mass of maleic anhydride, and the mass ratio of diethylenetriamine to 1,4-dioxane is 1:(4-5).

[0015] Furthermore, in step (2), the mass ratio of the prepolymer monomer to deionized water is 1:(5-8), and the mass of ethylenediamine is 10-15% of the mass of the prepolymer monomer.

[0016] Furthermore, in the step (3), the mass ratio of the polydopamine-coated carbon fiber to the amino-terminated hyperbranched polyamide aqueous solution is 1:(20-30), and the concentration of the amino-terminated hyperbranched polyamide aqueous solution is 2-4 mg / mL.

[0017] Furthermore, the preparation method of the flame retardant is as follows: Step A: Under nitrogen protection, DOPO, 4-maleimidobenzoic acid and N,N-dimethylformamide are mixed evenly, reacted at 90-100°C for 1-2h, and then heated to 125-135°C for 6-8h, cooled to room temperature, and recrystallized in an ice water bath for 12h. After vacuum filtration, washing and drying, modified DOPO is obtained; Step B: The modified DOPO, N,N-dimethylformamide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide are mixed evenly, stirred at 20-30° C. for 30-60 min, L-cysteine ​​is added, and stirring is continued for 12-24 h. After filtering, washing and drying, a flame retardant is obtained.

[0018] Furthermore, in step A, the mass ratio of DOPO, 4-maleimidobenzoic acid and N,N-dimethylformamide is 1:(1.0-1.2):(6-8).

[0019] Furthermore, in the step B, the mass ratio of modified DOPO, N,N-dimethylformamide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 1:(3-5):(0.08-0.10):(0.06-0.08).

[0020] Furthermore, in the step B, the mass of L-cysteine ​​is 1-2 times the mass of the modified DOPO.

[0021] Furthermore, the model of the antioxidant is German Brueggemann H161.

[0022] Furthermore, the model of the nucleating agent is German Brüggemann P22.

[0023] Furthermore, in step S1, the ultraviolet irradiation process conditions are: irradiation with 360-400nm ultraviolet rays for 30-60min, and an irradiation intensity of 20-35mW / cm 2 .

[0024] Furthermore, in step S2, the barrel temperatures of each section of the twin-screw extruder from section 1 to section 10 are 230-250°C, 270-290°C, 280-300°C, 290-310°C, 280-300°C, 270-290°C, 265-285°C, 265-285°C, 265-285°C, 285-305°C, the head temperature is 290-310°C, and the screw speed is 250-350rpm.

[0025] Compared with the prior art, the present invention has the following beneficial effects: 1. A high-strength modified plastic product and its preparation process of the present invention, using dopamine to modify the surface of carbon fiber to obtain polydopamine-coated carbon fiber, the introduction of the polydopamine layer not only improves the roughness of the carbon fiber surface, but also enhances the chemical activity of its surface, providing a platform for subsequent modification; maleic anhydride (MA) and diethylenetriamine (DETA) are used for amidation reaction to synthesize AB2 prepolymer monomer, and then central core ethylenediamine is introduced to obtain a hyperbranched polyamide compound containing carbon-carbon double bonds and terminal amino groups by a "one-step method", i.e., terminal amino groups. The introduction of amino-terminated hyperbranched polyamide provides a large number of amino groups and amide bonds. At the same time, the amino-terminated hyperbranched polyamide is grafted onto the surface of the carbon fiber through the Schiff base reaction between polydopamine and the amino group to obtain a modified carbon fiber containing a polyamide structural unit, which has good compatibility with the polyamide structure of polyphthalamide (PPA), significantly improves the dispersibility of the carbon fiber in the PPA matrix, and makes it have a better reinforcement effect, which is beneficial to improve the mechanical properties of the PPA products, thereby realizing high-strength and high-performance modified plastic products.

[0026] 2. A high-strength modified plastic product and a preparation process thereof of the present invention, wherein the active PH bond in the DOPO group is subjected to an addition reaction with the unsaturated double bond in 4-maleimidobenzoic acid to obtain DOPO containing a maleimide structure and a carboxyl group, i.e., modified DOPO, and then the carboxyl group on the surface of the modified DOPO is subjected to an amidation reaction with the amino group of L-cysteine ​​to introduce a thiol group, thereby obtaining a flame retardant containing N, P, and S elements; On this basis, a composite material was prepared by causing the carbon-carbon double bonds on the surface of modified carbon fibers to undergo a thiol-ene click reaction with the thiol groups in the flame retardant. This greatly improved the flame retardant properties of plastic products, while enhancing the structural strength of the material, effectively improving its safety and durability. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In this embodiment, the carbon fiber is short-cut carbon fiber, model is Japan Toray T300, length is 5-8mm; polyphthalamide is model is American DuPont HTN502; polyethylene wax is model is Honeywell AC-6A; antioxidant is model is German Brueggemann H161; nucleating agent is model is German Brueggemann P22.

[0029] In the following examples and comparative examples, 1 part is equal to 10 g.

[0030] Embodiment 1: A process for preparing a high-strength modified plastic product, comprising the following process: Step S1: 20 parts of modified carbon fiber, 10 parts of flame retardant, 2 parts of photoinitiator and 50 parts of N,N-dimethylformamide were mixed evenly, and irradiated with 360nm ultraviolet light for 30min with an irradiation intensity of 20mW / cm 2 , after washing and drying, a composite is obtained; Step S2: 35 parts of polyphthalamide, 30 parts of a composite, 0.2 parts of polyethylene wax, 0.2 parts of an antioxidant, and 0.3 parts of a nucleating agent are uniformly mixed to obtain a blend; the blend is melt-extruded, granulated, and injection-molded in a twin-screw extruder to obtain a modified plastic product; the barrel temperatures of the twin-screw extruder are 230° C., 270° C., 280° C., 290° C., 280° C., 270° C., 265° C., 265° C., 285° C. from section 1 to section 10, respectively; the die temperature is 290° C., and the screw speed is 250 rpm; The preparation method of modified carbon fiber is as follows: Step (1): adjusting the pH value of 0.01mol / LTris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a 2mg / mL dopamine hydrochloride solution; soaking 25 parts of carbon fibers in acetone for 22 hours to remove the surface sizing agent, washing with deionized water, and drying to obtain pretreated carbon fibers; immersing 25 parts of pretreated carbon fibers in 1250 parts of dopamine hydrochloride solution for 20 hours, taking out, and drying to obtain polydopamine-coated carbon fibers; Step (2): uniformly mix 1 part of maleic anhydride and 4 parts of 1,4-dioxane, dropwise add a mixed solution of 1.1 parts of diethylenetriamine and 4.4 parts of 1,4-dioxane, complete the dropwise addition for 1 hour, react at room temperature for 2 hours, distill under reduced pressure, and dry to obtain a prepolymer monomer; uniformly mix 1 part of the prepolymer monomer and 5 parts of deionized water, add 0.1 parts of ethylenediamine, react at 85°C for 4 hours, cool to room temperature, distill under reduced pressure, and dry to obtain an amino-terminated hyperbranched polyamide; Step (3): placing 25 parts of polydopamine-coated carbon fibers in 500 parts of a 2 mg / mL aqueous solution of amino-terminated hyperbranched polyamide, ultrasonically treating for 1 hour, reacting for 3 hours, filtering and drying to obtain modified carbon fibers; The preparation method of the flame retardant is as follows: Step A: Under nitrogen protection, 10 parts of DOPO, 10 parts of 4-maleimidobenzoic acid and 60 parts of N,N-dimethylformamide were mixed evenly, reacted at 90°C for 1 hour, and then heated to 125°C for 6 hours, cooled to room temperature, and recrystallized in an ice water bath for 12 hours. After vacuum filtration, washing and drying, modified DOPO was obtained; Step B: 10 parts of modified DOPO, 30 parts of N,N-dimethylformamide, 0.8 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.6 parts of N-hydroxysuccinimide were mixed evenly, stirred at 20°C for 30 minutes, 10 parts of L-cysteine ​​were added, and stirring was continued for 12 hours. After filtering, washing and drying, a flame retardant was obtained.

[0031] Embodiment 2: A process for preparing a high-strength modified plastic product, comprising the following process: Step S1: 35 parts of modified carbon fiber, 12 parts of flame retardant, 3 parts of photoinitiator and 80 parts of N,N-dimethylformamide were irradiated with 380nm ultraviolet light for 50min with an irradiation intensity of 30mW / cm 2 , after washing and drying, a composite is obtained; Step S2: 50 parts of polyphthalamide, 47 parts of the composite, 0.3 parts of polyethylene wax, 0.4 parts of an antioxidant, and 0.4 parts of a nucleating agent are mixed uniformly to obtain a blend; the blend is melt-extruded, granulated, and injection molded in a twin-screw extruder to obtain a modified plastic product; the barrel temperatures of the twin-screw extruder are 240°C, 280°C, 290°C, 300°C, 290°C, 280°C, 275°C, 275°C, 295°C from section 1 to section 10, respectively, the head temperature is 300°C, and the screw speed is 300rpm; The preparation method of modified carbon fiber is as follows: Step (1): adjusting the pH value of 0.01mol / LTris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a 4mg / mL dopamine hydrochloride solution; soaking 35 parts of carbon fiber in acetone for 23 hours to remove the surface sizing agent, washing with deionized water, and drying to obtain pretreated carbon fiber; immersing 35 parts of pretreated carbon fiber in 875 parts of dopamine hydrochloride solution for 22 hours, taking out, and drying to obtain polydopamine coated carbon fiber; Step (2): 2 parts of maleic anhydride and 9 parts of 1,4-dioxane are mixed evenly, and a mixed solution of 2.4 parts of diethylenetriamine and 10.8 parts of 1,4-dioxane is added dropwise for 1.5 hours, and the mixture is reacted at room temperature for 2.5 hours. After vacuum distillation and drying, a prepolymer monomer is obtained. 2 parts of the prepolymer monomer and 14 parts of deionized water are mixed evenly, and 0.24 parts of ethylenediamine are added. The mixture is reacted at 90° C. for 4.5 hours. After cooling to room temperature, vacuum distillation and drying, an amino-terminated hyperbranched polyamide is obtained. Step (3): placing 35 parts of polydopamine-coated carbon fibers in 875 parts of a 2 mg / mL aqueous solution of amino-terminated hyperbranched polyamide, ultrasonically treating for 1.5 h, reacting for 4 h, filtering, and drying to obtain modified carbon fibers; The preparation method of the flame retardant is as follows: Step A: Under nitrogen protection, 12 parts of DOPO, 13.2 parts of 4-maleimidobenzoic acid and 84 parts of N,N-dimethylformamide were mixed evenly, reacted at 95°C for 1.5 hours, and then heated to 130°C for 7 hours, cooled to room temperature, and recrystallized in an ice water bath for 12 hours. After vacuum filtration, washing and drying, modified DOPO was obtained; Step B: 12 ​​parts of modified DOPO, 48 parts of N,N-dimethylformamide, 1.08 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.84 parts of N-hydroxysuccinimide were mixed evenly, stirred at 25°C for 50 minutes, 18 parts of L-cysteine ​​were added, and stirring was continued for 20 hours. After filtering, washing and drying, a flame retardant was obtained.

[0032] Embodiment 3: A process for preparing a high-strength modified plastic product, comprising the following process: Step S1: 45 parts of modified carbon fiber, 15 parts of flame retardant, 4 parts of photoinitiator and 100 parts of N,N-dimethylformamide were irradiated with 400nm ultraviolet light for 60min with an irradiation intensity of 35mW / cm 2 , after washing and drying, a composite is obtained; Step S2: 65 parts of polyphthalamide, 60 parts of the composite, 0.4 parts of polyethylene wax, 0.6 parts of an antioxidant, and 0.5 parts of a nucleating agent are uniformly mixed to obtain a blend; the blend is melt-extruded, granulated, and injection molded in a twin-screw extruder to obtain a modified plastic product; the barrel temperatures of the twin-screw extruder are 250°C, 290°C, 300°C, 310°C, 300°C, 290°C, 285°C, 285°C, 305°C from section 1 to section 10, the die temperature is 310°C, and the screw speed is 350rpm; The preparation method of modified carbon fiber is as follows: Step (1): adjusting the pH value of 0.01mol / LTris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a 4mg / mL dopamine hydrochloride solution; soaking 45 parts of carbon fibers in acetone for 24 hours to remove the surface sizing agent, washing with deionized water, and drying to obtain pretreated carbon fibers; immersing 45 parts of pretreated carbon fibers in 900 parts of dopamine hydrochloride solution for 24 hours, taking out, and drying to obtain polydopamine-coated carbon fibers; Step (2): 3 parts of maleic anhydride and 15 parts of 1,4-dioxane are mixed evenly, and a mixed solution of 3.9 parts of diethylenetriamine and 19.5 parts of 1,4-dioxane is added dropwise for 2 hours, and the mixture is reacted at room temperature for 3 hours. After vacuum distillation and drying, a prepolymer monomer is obtained. 3 parts of the prepolymer monomer and 24 parts of deionized water are mixed evenly, and 0.45 parts of ethylenediamine are added. The mixture is reacted at 95° C. for 5 hours. After cooling to room temperature, vacuum distillation and drying, an amino-terminated hyperbranched polyamide is obtained. Step (3): placing 45 parts of polydopamine-coated carbon fibers in 1350 parts of a 2 mg / mL aqueous solution of amino-terminated hyperbranched polyamide, ultrasonically treating for 2 hours, reacting for 5 hours, filtering and drying to obtain modified carbon fibers; The preparation method of the flame retardant is as follows: Step A: Under nitrogen protection, 15 parts of DOPO, 18 parts of 4-maleimidobenzoic acid and 120 parts of N,N-dimethylformamide were mixed evenly, reacted at 100°C for 2 hours, and then heated to 135°C for 8 hours, cooled to room temperature, and recrystallized in an ice water bath for 12 hours. After vacuum filtration, washing and drying, modified DOPO was obtained; Step B: 15 parts of modified DOPO, 75 parts of N,N-dimethylformamide, 1.5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 1.2 parts of N-hydroxysuccinimide were mixed evenly, stirred at 30°C for 60 minutes, 30 parts of L-cysteine ​​were added, and stirring was continued for 24 hours. After filtering, washing and drying, a flame retardant was obtained.

[0033] Comparative Example 1: A process for preparing a high-strength modified plastic product, comprising the following processes: Step S1: 35 parts of carbon fiber, 12 parts of flame retardant, 3 parts of photoinitiator and 80 parts of N,N-dimethylformamide were irradiated with 380nm ultraviolet light for 50min with an irradiation intensity of 30mW / cm 2 , after washing and drying, a composite is obtained; Step S2: 50 parts of polyphthalamide, 47 parts of the composite, 0.3 parts of polyethylene wax, 0.4 parts of an antioxidant, and 0.4 parts of a nucleating agent are mixed uniformly to obtain a blend; the blend is melt-extruded, granulated, and injection molded in a twin-screw extruder to obtain a modified plastic product; the barrel temperatures of the twin-screw extruder are 240°C, 280°C, 290°C, 300°C, 290°C, 280°C, 275°C, 275°C, 295°C from section 1 to section 10, respectively, the head temperature is 300°C, and the screw speed is 300rpm; The preparation method of the flame retardant is as follows: Step A: Under nitrogen protection, 12 parts of DOPO, 13.2 parts of 4-maleimidobenzoic acid and 84 parts of N,N-dimethylformamide were mixed evenly, reacted at 95°C for 1.5 hours, and then heated to 130°C for 7 hours, cooled to room temperature, and recrystallized in an ice water bath for 12 hours. After vacuum filtration, washing and drying, modified DOPO was obtained; Step B: 12 ​​parts of modified DOPO, 48 parts of N,N-dimethylformamide, 1.08 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.84 parts of N-hydroxysuccinimide were mixed evenly, stirred at 25°C for 50 minutes, 18 parts of L-cysteine ​​were added, and stirring was continued for 20 hours. After filtering, washing and drying, a flame retardant was obtained; Compared with Example 2, the modified carbon fiber in Comparative Example 1 is replaced with carbon fiber of the same mass, and the other steps are the same as those in Example 2.

[0034] Comparative Example 2: A process for preparing a high-strength modified plastic product, comprising the following processes: Compared with Example 2, the flame retardant in Comparative Example 2 is replaced with DOPO of the same mass, and the other steps are the same as those in Example 2.

[0035] Comparative Example 3: A process for preparing a high-strength modified plastic product, comprising the following processes: Step S1: 12 parts of modified carbon fiber, 35 parts of flame retardant, 3 parts of photoinitiator and 80 parts of N,N-dimethylformamide are irradiated with 380nm ultraviolet light for 50min with an irradiation intensity of 30mW / cm2, washed and dried to obtain a composite; Step S2: 50 parts of polyphthalamide, 47 parts of the composite, 0.3 parts of polyethylene wax, 0.4 parts of an antioxidant, and 0.4 parts of a nucleating agent are mixed uniformly to obtain a blend; the blend is melt-extruded, granulated, and injection molded in a twin-screw extruder to obtain a modified plastic product; the barrel temperatures of the twin-screw extruder are 240°C, 280°C, 290°C, 300°C, 290°C, 280°C, 275°C, 275°C, 295°C from section 1 to section 10, respectively, the head temperature is 300°C, and the screw speed is 300rpm; Compared with Example 2, the composite of Comparative Example 3 includes the following components by weight: 12 parts of modified carbon fiber, 35 parts of flame retardant, 3 parts of photoinitiator, and 80 parts of N,N-dimethylformamide. Other steps are the same as those of Example 2.

[0036] Experiment: Take the modified plastic products obtained in Examples 1-3 and Comparative Examples 1-3, prepare samples, test their properties respectively and record the test results: Tensile performance test: tested in accordance with GB / T 1040.2-2006, dumbbell-shaped specimen, specimen size is 150m×10mm×4mm, and the tensile rate is 10mm / min; Bending performance test: tested in accordance with GB / T 9341-2008, specimen size is 80mm×10mm×4mm, and the load loading speed is 2mm / min; UL-94 flame retardant test: tested in accordance with GB / T 2408-2008, specimen size is 127.0mm×12.7mm×3.2mm.

[0037] The test results are as follows:

[0038] According to the data in the above table, we can clearly draw the following conclusions: Compared with Examples 1-3, the tensile strength and flexural strength of the product obtained in Comparative Example 1 are both reduced, indicating that the modified carbon fiber prepared by the present invention has better compatibility than carbon fiber, thereby effectively improving the mechanical properties of the material.

[0039] Compared with Examples 1-3, the flame retardant properties of the product obtained in Comparative Example 2 are reduced, which shows that compared with DOPO, the flame retardant prepared by the present invention has excellent flame retardant properties and can effectively improve the safety and fire resistance of the material.

[0040] Compared with Examples 1-3, the tensile strength and flexural strength of the product obtained in Comparative Example 3 are both reduced. It can be seen that when the addition amount of modified carbon fiber is reduced, the mechanical properties of the material will be reduced accordingly.

[0041] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A process for preparing a high-strength modified plastic product, characterized in that: The steps include: Step S1: uniformly mixing the modified carbon fiber, the flame retardant, the photoinitiator and N,N-dimethylformamide, irradiating with ultraviolet light, washing and drying to obtain a composite; Step S2: uniformly mixing polyphthalamide, the composite, polyethylene wax, an antioxidant and a nucleating agent to obtain a blend; melt-extruding, granulating and injection-molding the blend in a twin-screw extruder to obtain a modified plastic product.

2. The process for preparing a high-strength modified plastic product according to claim 1, characterized in that: The modified plastic product comprises the following components by weight: 35-65 parts of polyphthalamide, 30-60 parts of a composite, 0.2-0.4 parts of polyethylene wax, 0.2-0.6 parts of an antioxidant, and 0.3-0.5 parts of a nucleating agent.

3. The process for preparing a high-strength modified plastic product according to claim 2, characterized in that: The composite comprises the following components by weight: 20-45 parts of modified carbon fiber, 10-15 parts of flame retardant, 2-4 parts of photoinitiator and 50-100 parts of N,N-dimethylformamide.

4. The process for preparing a high-strength modified plastic product according to claim 3, characterized in that: The preparation method of the modified carbon fiber is as follows: Step (1): adjusting the pH of the Tris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a dopamine hydrochloride solution; The pretreated carbon fiber is immersed in a dopamine hydrochloride solution for 20-24 hours, taken out, and dried to obtain a polydopamine-coated carbon fiber; Step (2): uniformly mix maleic anhydride and 1,4-dioxane, dropwise add a mixed solution of diethylenetriamine and 1,4-dioxane, and complete the dropwise addition for 1-2 hours, react at room temperature for 2-3 hours, and obtain a prepolymer monomer after vacuum distillation and drying; uniformly mix the prepolymer monomer and deionized water, add ethylenediamine, react at 85-95° C. for 4-5 hours, cool to room temperature, and obtain an amino-terminated hyperbranched polyamide after vacuum distillation and drying; Step (3): placing the polydopamine-coated carbon fiber in an aqueous solution of amino-terminated hyperbranched polyamide, ultrasonically treating for 1-2 hours, reacting for 3-5 hours, filtering and drying to obtain modified carbon fiber.

5. The process for preparing a high-strength modified plastic product according to claim 4, characterized in that: The preparation method of the pretreated carbon fiber is as follows: The carbon fiber is soaked in acetone for 22-24 hours to remove the sizing agent on the surface, and then cleaned with deionized water and dried to obtain the pretreated carbon fiber.

6. The process for preparing a high-strength modified plastic product according to claim 3, characterized in that: The preparation method of the flame retardant is as follows: Step A: Under nitrogen protection, DOPO, 4-maleimidobenzoic acid and N,N-dimethylformamide are mixed evenly, reacted at 90-100°C for 1-2h, and then heated to 125-135°C for 6-8h, cooled to room temperature, and recrystallized in an ice water bath for 12h. After vacuum filtration, washing and drying, modified DOPO is obtained; Step B: The modified DOPO, N,N-dimethylformamide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide are mixed evenly, stirred at 20-30° C. for 30-60 min, L-cysteine ​​is added, and stirring is continued for 12-24 h. After filtering, washing and drying, a flame retardant is obtained.

7. The process for preparing a high-strength modified plastic product according to claim 6, characterized in that: In the step A, the mass ratio of DOPO, 4-maleimidobenzoic acid and N,N-dimethylformamide is 1:(1.0-1.2):(6-8).

8. The process for preparing a high-strength modified plastic product according to claim 1, characterized in that: In the step S2, the barrel temperatures of each section of the twin-screw extruder from section 1 to section 10 are 230-250°C, 270-290°C, 280-300°C, 290-310°C, 280-300°C, 270-290°C, 265-285°C, 265-285°C, 265-285°C, 285-305°C, the head temperature is 290-310°C, and the screw speed is 250-350rpm.

9. A high-strength modified plastic product obtained according to the preparation process according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for preparing a magnetic chain structure

    CN107531478A

  • Efficient PP flame-retardant master batch and preparation method thereof

    CN113248831A

  • Modified carbon fiber based on polydopamine film / nanosphere composite structure and preparation method thereof

    CN118345631A

  • High-rigidity low-warpage polyphthalamide material and preparation method thereof

    CN118652544A

Cited By

  • Environment-friendly composite fluoride-free flame-retardant polycarbonate material as well as preparation method and application thereof

    CN121406104A